In Vivo Cannabidiol Treatment Improves Endothelium-Dependent Vasorelaxation in Mesenteric Arteries of Zucker Diabetic Fatty Rats - Amanda J. Wheal; Amanda J. Wheal; Khalid Jadoon; Michael D. Randall; Saoirse E. O'Sullivan (Frontiers Media S.A., 2017)
Background and purpose: We have shown that in vitro treatment with cannabidiol (CBD, 2 h) enhances endothelial function in arteries from Zucker diabetic fatty (ZDF) rats, partly due to a cyclooxygenase (COX)-mediated mechanism. The aim of the present study was to determine whether treatment with CBD in vivo would also enhance endothelial function.Experimental approach: Male ZDF rats, or ZDF Lean rats, were treated for 7 days (daily i.p. injection) with either 10mg/kg CBD or vehicle (n = 6 per group). Sections of mesenteric resistance arteries, femoral arteries and thoracic aortae were mounted on a wire myograph, and cumulative concentration-response curves to endothelium-dependent (acetylcholine, ACh, 1 nM-100 μM) or endothelium-independent (sodium nitroprusside, SNP, 1 nM-100 μM) agents were constructed. Multiplex analysis was used to measure serum metabolic and cardiovascular biomarkers.Key results: Vasorelaxation to ACh was significantly enhanced in mesenteric arteries from CBD-treated ZDF rats, but not ZDF Lean rats. The enhanced vasorelaxation in ZDF mesenteric arteries was no longer observed after COX inhibition using indomethacin or nitric oxide (NO) inhibition using L-NAME. Increased levels of serum c-peptide, insulin and intracellular adhesion molecule-1 observed in the ZDF compared to ZDF Lean rats were no longer significant after 7 days CBD treatment.Conclusion and implications: Short-term in vivo treatment with CBD improves ex vivo endothelium-dependent vasorelaxation in mesenteric arteries from ZDF rats due to COX- or NO-mediated mechanisms, and leads to improvements in serum biomarkers.